When My Body Fails Me: Therapy for Women with Infertility - Costello, Leslie Ann (Bioenergetic Analysis, 2020)
This paper discusses the emotional processes that occur when a couple faces a diagnosis of infertility. There are gender differences in how people relate to this problem. Women’s experience of infertility may include pregnancy loss, medical intervention, and separation from the creative self. Issues that arise in therapy include the struggle with the diagnosis, coping with social relationships, grief and bereavement, and treatment decision-making. The treatments can alienate women from their bodies. A woman’s history of fertility struggles may underlie other reasons for being in therapy. The somatic focus of bioenergetic analysis is particularly helpful to women as they re-connect to the body through expressing a wide range and intensity of feelings. Case examples illustrate some of these points.